Pendidikan Berbasis Nilai-Nilai Islam Dalam Mewujudkan Generasi Berkarakter Unggul - Amelia Melviadyta Salsabila; Devina Dewi; Hubba Lillah AlMaula; Maliha Zakiyah Shalihah; Ummi Zahra; Asep Rudi Nurjaman (Program Studi Pendidikan Agama Islam, Universitas Muhammadiyah Bandung, 2024)
Education based on Islamic values is an educational approach that integrates Islamic values in all aspects of learning. The aim is to form a generation with superior character, namely a generation that has balanced intellectual, emotional and spiritual intelligence, and has noble morals. This article discusses the importance of education based on Islamic values in creating a generation with superior character. This article also discusses several educational models and strategies that can be implemented to realize this goal. The research results show that education based on Islamic values has a significant influence on the formation of students' character. Students who follow education based on Islamic values show better behavior, such as honesty, discipline and responsibility. Apart from that, they also have higher learning achievements. Based on the results of this research, it can be concluded that education based on Islamic values is one solution to creating a generation with superior character.